Ex Vivo Expansion of Human Limbal Epithelial Cells Using Human Placenta-Derived and Umbilical Cord-Derived Mesenchymal Stem Cells. (15th August 2017) - Nam, Sang Min; Maeng, Yong-Sun; Kim, Eung Kweon; Seo, Kyoung Yul; Lew, Helen
Abstract : Ex vivo culture of human limbal epithelial cells (LECs) is used to treat limbal stem cell (LSC) deficiency, a vision loss condition, and suitable culture systems using feeder cells or serum without animal elements have been developed. This study evaluated the use of human umbilical cord or placenta mesenchymal stem cells (C-MSCs or P-MSCs, resp.) as feeder cells in an animal/serum-free coculture system with human LECs. C-/P-MSCs stimulated LEC colony formation of the stem cell markers (p63, ABCG2) and secreted known LEC clonal growth factors (keratinocyte growth factor, β -nerve growth factor). Transforming growth factor- β -induced protein (TGFBIp), an extracellular matrix (ECM) protein, was produced by C-/P-MSCs and resulted in an increase in p63 + ABCG2 + LEC colonies. TGFBIp-activated integrin signaling molecules (FAK, Src, and ERK) were expressed in LECs, and TGFBIp-induced LEC proliferation was effectively blocked by a FAK inhibitor. In conclusion, C-/P-MSCs enhanced LEC culture by increasing growth of the LSC population by secreting growth factors and the ECM protein TGFBIp, which is suggested to be a novel factor for promoting the growth of LECs in culture. C-/P-MSCs may be useful for the generation of animal-free culture systems for the treatment of LSC deficiency.